Principles of state financial control of Ukraine in the conditions of european integration - Pustovit, Juliya; Timashov, Viktor; Berger, Alina (My University, 2018)
The purpose of the study is improvement of principles of state financial control of Ukraine taking into account European advanced experience. The subject of the research is comparative analysis of financial control principles and principles of state financial control of Ukraine with the international principles of financial control, envisaged at the international level, and establishment of expediency of their implementation in the national legislation in connection with the terms of Eurointegration.The methodological background of the research his the combination of theoretical and scientific methods: analysis, synthesis and comparison, theoretical and logical generalization. The theoretical approaches are analyzed according to the determination of concept-category of terms: “principle of financial control”, “principle of state financial control”. Existed principles of financial control, principles of state financial control of Ukraine, leading principles of financial control, what determined in Lima Declarations of Guidance on Auditing Precepts, general principles of supreme bodies of financial control activity that envisaged in Declaration about general principles of supreme bodies of financial control activity of states-participants of CISare investigated. Carrying out the analysis of financial control principles, principles of state financial control of Ukraine and international principles of financial control, reached to the conclusion, that basic principles (principles of legality, independence, objectivity, impartiality, publicity, neutrality) are already normatively envisaged. There is the part of international principles (principle of competence, publicity, efficiency, well-proven, observance of professional ethics, violation prevention, obligatory of responsibility offensive for the accomplished violations of financial discipline) that doesn’t have the normative fixing in the normatively-legal acts of Ukraine. International principles of financial control are partly marked in scientific literature of Ukraine, but it not enough in order that they become leading ideas, fundamental basis of the financial control system development of European standard in Ukraine. Conclusions. It is suggested to improve the normatively-legislative providing of state financial control: to manage further development of conceptual bases of the system of state financial control principles, their classification; in branch legislation to specify principles of state financial control in accordance with their kinds; to complement Law of Ukraine “On basic principles of state financial control realization in Ukraine”. The list of realization principles of state financial control in Ukraine that will become one of the meaningful steps on the way of Eurointegration of Ukraine to European Union is envisaged. Метою дослідженняє вдосконалення принципів державного фінансового контролю України з урахуванням Європейського передового досвіду з даного питання. Об’єктом дослідження: є порівняльний аналіз принципів фінансового контролю і принципів державного фінансового контролю України з міжнародними принципами фінансового контролю, закріпленими на міжнародному рівні, а також встановлення доцільності їх імплементації в національне законодавство у зв'язку з умовами євроінтеграції. Методологія дослідження - це сукупність теоретичних і загальнонаукових методів: аналіз, синтез і порівняння, теоретичне та логічне узагальнення. У роботі аналізуються теоретичні підходидо визначення понятійно-категоріального змісту термінів: «принцип фінансового контролю», «принцип державного фінансового контролю». Досліджено існуючі принципи фінансового контролю, принципи державного фінансового контролю України, керівні принципи фінансового контролю, які визначені в Лімській декларації керівних принципів фінансового контролю, загальні принципи діяльності вищих органів фінансового контролю, що закріплені в Декларації про загальні принципи діяльності вищих органів фінансового контролю держав-учасниць СНД. Здійснивши аналіз принципів фінансового контролю, принципів державного фінансового контролю України та міжнародних принципів фінансового контролю, дійшли до висновку, що основні принципи (принцип законності, принцип незалежності, принцип об’єктивності, принцип безсторонності, принцип гласності, принцип неупередженості) є вже нормативно закріпленими. Також є частина міжнародних принципів (принцип компетентності, принцип публічності, принцип ефективності, принцип оперативності, принцип доведеності, принцип дотримання професійної етики, принцип запобігання порушенням, принцип обов’язковості настання відповідальності за скоєні порушення фінансової дисципліни), які не мають нормативного закріплення в нормативно-правових актах України. Частково зазначені міжнародні принципи фінансового контролю зустрічаються в науковій літературі України, але цього недостатньо для того, щоб вони стали керівними ідеями, фундаментальною основою побудови системи фінансового контролю в Україні європейського зразку. З огляду на проведене дослідження, пропонується удосконалити нормативно-законодавче забезпечення державного фінансового контролю: вести подальшу розробку концептуальних основ системи принципiв державного фiнансового контролю, їх класифікації; у галузевому законодавстві конкретизувати принципи державного фiнансового контролю відповідно до їх видів; доповнити Закон України «Про основні засади здійснення державного фінансового контролю в Україні» статтею, в якій передбачити перелік принципів здійснення державного фінансового контролю в Україні (законність, незалежність, об’єктивність, оперативність, доведеність, ефективність, компетентність, дотримання професійної етики, гласність, публічність, запобігання порушенням, обов’язковість настання відповідальності за скоєні порушення фінансової дисципліни), що стане одним із значущих кроків на шляху євроінтеграції України до Європейського Союзу.
Keywords: кафедра маркетингу; control; financial control; state financial control; principles of financial control; principles of state financial control; контроль; фінансовий контроль; державний фінансовий контроль; принципи фінансового контролю; принципи державного фінансового контролю